Interactive Game Model in Drill and Practice Learning to Increase Student Learning Achievement - Najih, Ahmad; Futihah, Amanda (Universitas Amikom Purwokerto, 2024)
In order to enhance student learning outcomes, this research attempts to develop multimedia learning using a drill and practice methodology. The research and development approach, also known as research and development (R&D), was employed in this study. Assess the media's performance and determine how feasible it is to test this game in real-world settings. It is intended that this game would contribute to better learning outcomes for students. Along with determining students' opinions and interests in learning through drill-and-practice multimedia learning methods, this study also seeks to ascertain the viability and validity of the created interactive quiz game as well as students' evaluations of the multimedia. A field survey administered to middle school students and a student assessment questionnaire for interactive quiz games were the two types of questionnaires employed in this study. The study's findings showed that nearly all students responded favourably to learning that combined interactive quiz games with drill and practice multimedia learning models; additionally, students evaluated the interactive multimedia learning quiz games extremely well, scoring 91.979% on the assessment scale; and learning outcomes increased.